Knowledge and skills on active management of third stage of labor for prevention of post-partum haemorrhage among health care providers in Lake Zone, Tanzania: a cross sectional study - Daniel Lugwesa Muyanga; Angelina A. Joho (BMC, 2022)
Abstract Background Health care providers (HCPs) knowledge and skills are both crucial in saving the lives of mothers and their newborns during childbirth. This study aimed to assess the knowledge and skills of HCPs on active management of third stage of labor (AMTSL) for prevention of PPH in Lake Zone Tanzania. Methods A cross-sectional analytical hospital-based study which included 340 HCPs who were randomly selected, the study was conducted from March to May 2019 in lake zone, Tanzania. Data were collected using standardized questionnaire and observational checklist. Predictors of knowledge and skills on AMTSL were determined using binary logistic regression under multivariable analysis using SPSS version 23.0. p-value less than 0.05 was considered significant. Results Most 200 (58.8%) of the participants were aged between 25 and 34 years with mean age 31.4 ± 6.26 years. Majority 240 (67.6%) were females. Of all HCPs, 171 (50.3%) had adequate knowledge whereas 153 (45.0%) had adequate skills on AMTSL. Males (AOR = 1.96, 95% CI 1.18-3.26), HCPs with University education (AOR = 3.29, 95% CI 1.19-9.13) and previous BEmONC training (AOR = 2.20, 95% CI 1.24-3.91) were found to be the predictors of adequate knowledge on AMTSL. HCPs aged ≥ 45 years (AOR = 9.35, 95% CI 1.74-10.28) and HCPs working at a hospital (AOR = 1.78, 95% CI 1.12-2.82) were associated with having adequate skills on AMTSL. Conclusion HCPs included in this study demonstrated low skills on AMTSL as compared to knowledge which needs immediate attention. We recommend continuous in-service training and supportive supervision among HCPs working in labour wards for improving their knowledge and skills on AMTSL. This will help to reduce maternal morbidity and mortality related to PPH.